A prospective analysis of lymph node retrieval in colorectal cancer: discrepancies, neoadjuvant impact, and practical implications - Biswas, Saumik; Walsh, Jesse R.; Ul Haq, Sami; Marilley, Ann M.; Pasman, Elizabeth P.; Kendall, Monica; Cecchini, Matthew; Lebbin, Grace; Wilson, Darren (Frontiers in Medicine, 2025)
IntroductionAccurate lymph node (LN) retrieval is vital for colorectal cancer (CRC) staging and determining adjuvant therapy.MethodsIn this prospective study of 122 CRC specimens, we evaluated LN retrieval times, discrepancies between gross and microscopic LN counts, and the impact of neoadjuvant therapy.ResultsOn average, dissecting each specimen took 50 min (range 15–295 min), with rectal and descending/sigmoid colon specimens often requiring multiple passes. Macroscopic dissection yielded an average of 45.1 LNs per specimen, whereas microscopic examination confirmed only 35.7 LNs on average. Neoadjuvant therapy did not alter macroscopic yields (p = 0.105), yet significantly reduced microscopic LN counts (p = 2.676 × 105). T-stage correlated with total microscopic LN counts (p = 0.018) but not the number of cancer-positive nodes (p = 0.140). Rectal specimens showed the largest discrepancy between macroscopic and microscopic LN counts; in contrast, 8 specimens had higher microscopic than macroscopic counts, suggesting that some LNs were missed during manual palpation but detected microscopically in the extra submitted sections of mesenteric tissue. Overall, the mean absolute percentage error (MAPE) was 50.18%, rising to 97.87% for neoadjuvant-treated cases. The average pathology report turnaround time (TAT) was 3.3 business days, meeting the recommended 4-days threshold, with no significant delay due to cancer location or additional LN searches. A preliminary cost analysis indicates that missed or misidentified LNs can increase histology processing and pathologist review expenses, emphasizing the need for more efficient LN search protocols.DiscussionTaken together, these findings emphasize the multifactorial nature of LN retrieval challenges, particularly in neoadjuvant-treated and anatomically complex cases. Refining dissection protocols, leveraging new technologies, and allocating adequate resources may help reduce retrieval errors, potentially improving staging accuracy and clinical decision-making.